Die voortgaande gesprek rakende Christelike denke (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2025)
Does it make sense to discern a link or connection between Christian convictions and scholarly activities? The widely popular conception is still that science merely designates the discipline of physics and perhaps also mathematics as an intellectual enterprise. During my second last year at school our history teacher explained to us the slogan of the French Revolution. Back home I asked my father about his explanation and then my father came up with an alternative view which made more sense to me. He related it to the political philosophy of John Locke and Jean Jacques Rousseau. My next question was why this explanation is not found in the history textbooks at school? He’s response was that it is the case because the history teachers are not well versed in political philosophy. And this prompted me to ask the question I should not have asked, namely: What is philosophy? In the course of our subsequent discussions it became clear to me that philosophy is actually the foundational discipline among all the subjects one can study at university level. Not even a question such as what is science could be answered by a specific special science. Moreover, the history of any specific subject one can study at university is embedded in the dominant trends of thought operative within the history of the special sciences and philosophy. At the time I discovered that there was a lively discussion present in certain philosophical circles within South Africa. Professor EA Venter from the University of the Orange Free State published a book on the main contours of the history of philosophy. A critical review was written by Dr Johan Degenaar which prompted the editorial board of the journal Gereformeerde Vaandel (1956) to invite Degenaar to write an article on Dooyeweerd and his transcendental critique of theoretical thought. In his response to Degenaar Venter focused on the way in which his approach to philosophy promoted his own philosophical stance as an embodiment of “modern thought”. Venter challenged this claim with reference to the multiple branches of modern thought where Degenaar and his philosophical orientation could merely be seen as a branch of one of the three main trends in modern philosophy or perhaps a branch of such a branch. This inspired me to write this article directing my attention on similar instances in my own experience of discussions surrounding the issue of Christianity and scholarly thinking. In 1969 I visited the Stellenbosch University and then participated in a discussion organised on campus about the possibility of Christian scholarship. My discussion partner was André du Toit who also belonged to the philosophy department of the University of Stellenbosch. The key issue of the discussion was whether or not any scholar who does not accept the logical principles of identity, non-contradiction and the excluded middle could participate in the game of science. However, in the school of intuisionistic mathematics the logical principle of the excluded middle is not accepted in the case of infinite totalities. This opened the way for an approach to scholarship in which another principle comes to the fore, namely the principle of the excluded antinomy – to which we shall return in a follow-up article on a non-reductionist ontology. Another example explored in this article briefly gives an account of the significance of factual critique and immanent critique coupled with an illustration of the relativising effect of the history of scholarly disciplines. In passing I have briefly mentioned the establishment of a special chair in reformational philosophy at Rhodes University of South Africa. This article concludes by mentioning historically significant schools of thought within some natural sciences.